Pengaruh Kelas Ibu Hamil Terhadap Kecemasan Pada Ibu Primigravida Di Desa Parmonangan Kabupaten Samosir - Rinse Waty Haloho; Nopalina Suyanti Damanik; Parningotan Simanjuntak; Anna Waris Nainggolan (NAJ Nursing Applied Journal, 2024)
Factors that influence anxiety in pregnant women include lack of family support, financial adequacy, stress from the environment, high frequency of nausea and vomiting (physical health factors of pregnant women), attitudes towards pregnancy and ability to control pregnancy, good adjustment process to pregnancy. physically and psychosocially, as well as information about frightening birth experiences from the environment. (Andriana, 2016) This research aims to determine the influence of the class of pregnant women on anxiety among primigravida mothers in Parmonangan Village, Samosir Regency in 2023. This research uses a quantitative research design using correlational research and a cross-sectional approach, the population and sample size are primigravida mothers with a gestational age of 8-37 weeks in Parmonangan Village, Samosir Regency, namely 40 people using the total sampling method in April-June 2023. Analysis uses the Chi Square test for significance and if the p-value is > 0.05. Based on the results of the Chi Square statistical test research, the p value = 0.001, so p > 0.05, means H0 is rejected and Ha is accepted. This means that there is a relationship between the class of pregnant women and primigravida anxiety at the Tanjung Pura District Hospital, Langkat Regency based on Spearman's rho calculations with ᾳ = 0.05, a p value of 0.010 is obtained because the p value < ᾳ means that the test results are statistically significant, or reject Ho. described that pregnant women who attended classes for pregnant women had mild levels of anxiety. It is hoped that this will provide information about the implementation of pregnancy classes for primigravida mothers in reducing anxiety about their pregnancy